2021
DOI: 10.1007/s11145-021-10185-y
|View full text |Cite
|
Sign up to set email alerts
|

Handwriting fluency and the quality of primary grade students’ writing

Abstract: Until children can produce letters quickly and accurately, it is assumed that handwriting disrupts and limits the quality of their text. This investigation is the largest study to date (2596 girls, 2354 boys) assessing the association between handwriting fluency and writing quality. We tested whether handwriting fluency made a statistically unique contribution to predicting primary grade students’ writing quality on a functional writing task, after variance due to attitude towards writing, students’ language b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 59 publications
4
32
0
1
Order By: Relevance
“…Each trait was scored using a separate 1 to 5 rating scale. The rating scaled were developed and validated for use in Grades 1–3 by Skar, Jølle, and Aasen (2020), and also used in Skar et al (2021), who reported that, on average, girls outperformed boys, and students in higher grades outperformed students in lower grades. Higher scores represented better quality for the trait assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Each trait was scored using a separate 1 to 5 rating scale. The rating scaled were developed and validated for use in Grades 1–3 by Skar, Jølle, and Aasen (2020), and also used in Skar et al (2021), who reported that, on average, girls outperformed boys, and students in higher grades outperformed students in lower grades. Higher scores represented better quality for the trait assessed.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of our study was to explore audience awareness characteristics in elementary school students' texts. Based on previous research into the same student group (Skar, Lei, et al, 2021), we expected to find considerable variation within and between grades. Therefore, we posed the following two research questions:…”
Section: Aims and Research Questionsmentioning
confidence: 99%
“…The corpus constituted a representative sub-sample of a large pool of texts (N = 6,058) that were written by students in grades 1-3 (aged 6-8 years) and were scored for text quality (see Skar, Lei, et al, 2021, for details on the scoring procedure and the representativeness of the larger sample; see Skar, Kvistad et al, 2021, for information on the scoring criteria). The corpus used in the present investigation was representative in terms of score groups.…”
Section: Data Sources and Sampling Strategymentioning
confidence: 99%
See 2 more Smart Citations